A bibliometric analysis of research on zakat: Past trends and future directions - Luqman Hakim Handoko; Ai Nur Bayinah; Firmansyah Firmansyah (al-Uqud : Journal of Islamic Economics, 2022)
Zakat is a part of Islamic social finance that aimed at the social purpose and has been recently received attention from researchers globally. Therefore, the study aimed to explore the current state of zakat literature, identify the bibliometrics in the field, and provide future research direction. To achieve this goal, this study utilised bibliometric analysis using VOSviewer software. The documents were extracted from the Scopus database on 5th March 2021 with the search keyword Zakat and its variations. The result showed 635 documents in 267 journals and revealed approximately 1289 authors. The papers came from 53 countries and 160 affiliations roughly. Based on co-occurrence, the analysis identified 1488 keywords and the word zakat, Islam, Malaysia, Poverty, and zakat institution as the top five frequent keywords. The study also revealed the current trend of zakat studies related to education, performance, SME, and compliance. The most important of this study, seventeen zakat issues, were provided for future research agenda. Henceforth, the following research might focus on this study's suggestions to enrich and enhance zakat literature.